2003
DOI: 10.4049/jimmunol.170.4.2106
|View full text |Cite
|
Sign up to set email alerts
|

IL-17, Produced by Lymphocytes and Neutrophils, Is Necessary for Lipopolysaccharide-Induced Airway Neutrophilia: IL-15 as a Possible Trigger

Abstract: IL-17 is a cytokine implicated in the regulation of inflammation. We investigated the role of this cytokine in neutrophil recruitment using a model of LPS-induced lung inflammation in mice. In the bronchoalveolar lavage, LPS induced a first influx of neutrophils peaking at day 1, followed by a second wave, peaking at day 2. IL-17 levels were increased during the late phase neutrophilia (day 2), and this was concomitant with an increased number of T cells and macrophages, together with an increase of KC and mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
357
4
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(387 citation statements)
references
References 39 publications
19
357
4
7
Order By: Relevance
“…It was also shown that IL-15 induced IL-17 production from splenic CD4 + cells in BALB/c mice [32]. Thus, IL-17 may also be involved in the IL-15-mediated pathogenesis of chronic arthritis in both humans and mice.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It was also shown that IL-15 induced IL-17 production from splenic CD4 + cells in BALB/c mice [32]. Thus, IL-17 may also be involved in the IL-15-mediated pathogenesis of chronic arthritis in both humans and mice.…”
Section: Introductionmentioning
confidence: 94%
“…3B). These results suggest that CD4 + T cells expressing functional IL-23R and producing IL-17 were increased in IL-15 Tg mice at the chronic phase of CIA.IL-15 has been shown to be a potent enhancer of IL-17 production from CD4 + T cells in vitro [31,32]. The results of these studies and our results raise the possibility that IL-15 has an activity to enhance Agspecific IL-17 production in addition to a bystander production of IL-17 in response to IL-23 as shown above.…”
mentioning
confidence: 89%
“…Furthermore, although T cells are a major source of IL-17, they are not the only source of this cytokine. Neutrophils, as well as T cells, have been shown to produce IL-17 in response to IL-15 [23]. In addition, the precise subpopulation(s) of T cells that secrete IL-17 remain unclear.…”
Section: T-cell Subtypes That Secrete Il-17mentioning
confidence: 99%
“…The IL-17A and F are produced by a class of effectors αβ T cells (Th17 and CD8+ cells), NK cells and neutrophils (Ciric et al, 2009;Michel et al, 2008;Weaver et al, 2007). They induce the expression of numerous inflammatory mediators including IL-8, CXC chemokines, granulocyte-colony stimulating factor and prostaglandin E2 (Ferretti et al, 2003;Jones and Chan, 2002;Ruddy et al, 2004). IL-17 displays proinflammatory properties, like those of tumour necrosis factor α (TNFα), in its capacity to induce other inflammatory effectors (Benderdour et al, 2002;Gaffen, 2004), and synergizes with other cytokines at the center of the inflammatory network (Gaffen, 2004) to activate the nuclear factor κB (Hata et al, 2002).…”
Section: Introductionmentioning
confidence: 99%